(untitled) - James, Amy (San Francisco, 2008)
A new book in the Knowledge Essential series, School Success for Children with Special Needs offers parents a guide for understanding and navigating the often-confusing special education system to ensure that your child gets the best education possible. It tells you: How to know if your child has a physical, learning, or emotional disability; How the latest changes to the Individuals with Disabilities in Education Act (IDEA), the Americans with Disabilities Act (ADA), and the No Child Left Behind Act (NCLB) effect your child's education; How to help formulate your child's Individual Family Services Plan (IFSP) or Individualized Education Program (IEP); Information on the many ways schools and teachers can accommodate for children with disabilities; How to assess our child's progress; How can you help your child be successful at school and in life by reinforcing basic skills at every age; How to plan for transitioning your child to the wider world; The kind of paperwork you can expect to encounter.
Keywords: Children with disabilities,Special education; Education,Parent participation